Forest Protection through Sasi: Local Environmental Law in Ambon Island Post COVID -19 Pandemic - Aarce Tehupeiory; Haposan Sahala Raja Sinaga; Lamhot Naibaho (University of Udayana, 2021)
This study discusses forest protection through Sasi (Local Environmental Law) in Ambon island post-COVID-19. Sasi is a customary norm and rules and sanctions regarding the prohibition of taking plant or plant products, fish and game time before the time agreed and determined by community leaders and leaders together with community members. The main goal is to conserve natural resources, control and limit human greed in overexploiting natural resources. The research method used is a qualitative research method with normative legal research. The research was conducted at Universitas Kristen Indonesia from January to March 2021. The objects studied were documents either in reports or regulations related to indigenous peoples' local wisdom. The research instrument used was a document checklist. The data analysis technique used is the descriptive analysis technique. The research results are that traditional Sasi wisdom has values ??and norms to protect forests, water sources, annual plants, and food plants. With the concept and understanding of how environmental managements with various customary rules to obtain benefits and maintain the kinship value of area units that already have an identity and must continuously be maintained in the aftermath of the COVID-19 pandemic.